2015
DOI: 10.1007/s10336-015-1201-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of year-to-year variation in haemoglobin and glucose concentrations in the blood of nestling Pied Flycatchers Ficedula hypoleuca

Abstract: Physiological tools can be used to identify the sources and consequences of stressors on animals. Understanding the influences of variation in habitat quality and anthropogenic disturbance on organism condition and health may improve future management and conservation. We present results concerning variation in haemoglobin and glucose concentrations in the blood of about 14-day-old nestling Pied Flycatchers Ficedula hypoleuca in central Poland over a 4-year period, 2011-2014, in a deciduous forest. The most im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Repeatability is low if measurements within broods are very different (Bańbura and Zieliński 1990). The high repeatability of haemoglobin concentration we found suggests that hemoglobin responds first of all to the factors affecting entire broods, such as parasitic pressure in the nest (Glądalski et al 2015a). More studies are needed to determine if this may be considered as a general pattern in wild populations of birds.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Repeatability is low if measurements within broods are very different (Bańbura and Zieliński 1990). The high repeatability of haemoglobin concentration we found suggests that hemoglobin responds first of all to the factors affecting entire broods, such as parasitic pressure in the nest (Glądalski et al 2015a). More studies are needed to determine if this may be considered as a general pattern in wild populations of birds.…”
Section: Discussionmentioning
confidence: 80%
“…Some recent studies suggest caution when using haemoglobin concentration as a simple body condition index (Lill et al 2013). However, our previous studies showed that the level of haemoglobin is a reliable condition indicator for Tits (Nadolski et al 2006;Kaliński et al 2009;Kaliński et al 2012) and for Pied Flycatcher (Glądalski et al 2015a). Kilgas et al (2006a, b) also found that the concentration of haemoglobin is strongly positively related to the physiological condition of nestling great tits.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations